Wawasan Hadis Tentang Tasamuh Kajian tentang Perlindungan Perempuan dan Anak-Anak dalam Perang - Sabir, Muhammad (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2013)
Islamic rules of war refers to what has been received in the sharia (Islamic law) and fiqh (Islamic jurisprudence) by the ulama (Islamic scholars) as the right way in Islam that must be obeyed by the Muslims in the air while the war. is clear that Islam regards non-Muslim parties not from the standpoint of hatred, bigotry and arrogance. However, the attitude of Islam to non-Muslims who are not hostile to any Islam based on tolerance, cooperation, brotherhood in the name of humanity, in the name of humanity and respect, and respect for all treaties and agreements